2016
DOI: 10.1002/lary.26191
|View full text |Cite
|
Sign up to set email alerts
|

Palatal botulinum toxin as a novel therapy for objective tinnitus in forced eyelid closure syndrome

Abstract: Objective tinnitus associated with eyelid closure is a rare clinical entity with only a few reported cases. This association previously was identified as forced eyelid closure syndrome (FECS) and involves an aberrant neural reflex between cranial nerve VII (activating the orbicularis oculi muscle) and cranial nerve V (activating the tensor tympani muscle). We present a 52-year-old Caucasian female with a 2-month history of FECS who was successfully treated with intrapalatal botulinum toxin, with full resolutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The large effect of eye blinking on the middle ear admittance suggested that the admittance change resulted from the TTM contraction (the admittance change related to SM contraction alone is much smaller—Kim et al., 2015). This phenomenon has been described in the literature is called the forced eyelid closure syndrome and can be associated to tinnitus ( Kaffenberger, Mandal, Schaitkin, & Hirsch, 2017 ; Kim et al., 2015 ; Lee et al., 2012 ; Ohki & Kato, 2012 ; Rock, 1995 ). The mechanisms of the forced eyelid closure syndrome are unclear.…”
Section: A Pathophysiological Model Of Tttsmentioning
confidence: 99%
“…The large effect of eye blinking on the middle ear admittance suggested that the admittance change resulted from the TTM contraction (the admittance change related to SM contraction alone is much smaller—Kim et al., 2015). This phenomenon has been described in the literature is called the forced eyelid closure syndrome and can be associated to tinnitus ( Kaffenberger, Mandal, Schaitkin, & Hirsch, 2017 ; Kim et al., 2015 ; Lee et al., 2012 ; Ohki & Kato, 2012 ; Rock, 1995 ). The mechanisms of the forced eyelid closure syndrome are unclear.…”
Section: A Pathophysiological Model Of Tttsmentioning
confidence: 99%